2017
DOI: 10.12659/msm.904802
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of Percutaneous Balloon Kyphoplasty for the Treatment of Symptomatic Schmorl’s Nodes: 5-Year Results

Abstract: BackgroundDespite literature supporting the efficiency of percutaneous balloon kyphoplasty (PKP) in treating osteoporotic and malignant vertebral compression fractures, few reports exist that document its use for treatment of symptomatic Schmorl’s nodes (SNs) refractory to conservative treatment. Patients with symptomatic SNs could have pain in the vertebrae similar to an acute vertebral compression fracture. MRI is very helpful in diagnosing symptomatic SNs when x-ray and CT scan are unremarkable. In painful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 21 publications
(43 reference statements)
0
20
0
Order By: Relevance
“…According to previous studies, SNs could cause severe back pain through the release of inflammatory mediators or cause adjacent endplate fractures [7,12]. Although the precise relationship between SNs and back pain remain unclear, a specific subgroup of patients with SNs whose spinal MRI showed a high signal intensity on fat-suppression sequences in the vertebral endplate surrounding the SNs, appear to have severe low back pain that originated from the edematous vertebral endplate [18][19][20][21][22][23][24]. The same signal changes in MRI images were defined as inclusion criteria in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to previous studies, SNs could cause severe back pain through the release of inflammatory mediators or cause adjacent endplate fractures [7,12]. Although the precise relationship between SNs and back pain remain unclear, a specific subgroup of patients with SNs whose spinal MRI showed a high signal intensity on fat-suppression sequences in the vertebral endplate surrounding the SNs, appear to have severe low back pain that originated from the edematous vertebral endplate [18][19][20][21][22][23][24]. The same signal changes in MRI images were defined as inclusion criteria in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Because for patients with severe osteoporosis, they do not need a clear traumatic history to develop VCFs, and slight impacts to the spine such as coughing and lifting heavy stuff could lead to bone fractures and result in severe back pain. Based on previous studies, patients with painful SNs who are refractory to conservative treatment show improvement through several surgical procedures including discoblock, percutaneous vertebroplasty, spinal fusion, and tumor necrosis factor alpha (TNF-a) inhibition [18][19][20][21][22][23][24][25][26]. The use of these surgical options is based on the causative factors of low back pain, generated from endplate fractures or from degenerative disc materials that result in a special type of discogenic back pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies suggested to insert the working cannulas directed towards the apex of the SNs to fill the polymethylmethacrylate (PMMA) around the profile of the SNs in an eggshell shape [18,21]. However, studies highlighting these procedures are limited to retrospective studies study [18][19][20][21][22][23][24]. Hence, In our study, we treated 65 patients with severe back pain by PVP that were suspected to be secondary to fresh endplate fractures (with high signal intensity on fat-suppression sequences in spinal MRI) around SNs.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…Vertebral compression fractures are common in the elderly population [16,17], and PVP could obtained satisfactory clinical results. To-date, the outcomes of painful SNs with endplate fractures treated by PVP are less well studied and limited to retrospective studies of small sample sizes [18][19][20][21][22][23][24].…”
mentioning
confidence: 99%